Ampicillin and Ceftobiprole Combination for the Treatment of Enterococcus faecalis Invasive Infections: “The Times They Are A-Changin” - Simone Giuliano; Jacopo Angelini; Denise D’Elia; Monica Geminiani; Roberto Daniele Barison; Alessandro Giacinta; Assunta Sartor; Floriana Campanile; Francesco Curcio; Menino Osbert Cotta; Jason A. Roberts; Massimo Baraldo; et al. (Antibiotics, 2023)
Background: Enterococcus faecalis is responsible for a large variety of severe infections. This study is a case series reporting our experience in the treatment of E. faecalis invasive infections with ampicillin in combination with ceftobiprole (ABPR). Methods: We retrospectively analyzed all the medical records of patients admitted to the University Hospital of Udine from January to December 2020 with a diagnosis of infective endocarditis or primary or non-primary complicated or uncomplicated bacteremia caused by E. faecalis. Results: Twenty-one patients were included in the final analysis. The clinical success rate was very high, accounting for 81% of patients, and microbiological cure was obtained in 86% of patients. One relapse was recorded in one patient who did not adhere to the partial oral treatment prescribed. Therapeutic drug monitoring (TDM) was always performed for ampicillin and ceftobiprole, and serum concentrations of both drugs were compared to the MICs of the different enterococcal isolates. Conclusions: ABPR is a well-tolerated antimicrobial regimen with anti-E. faecalis activity. TDM can help clinicians optimize medical treatments to achieve the best possible efficacy with fewer side effects. ABPR might be a reasonable option for the treatment of severe invasive infections caused by E. faecalis due to the high level of enterococcal penicillin-binding protein (PBP) saturation.